Benzimidazol-2-ylidene gold(I) complexes are thioredoxin reductase inhibitors with multiple antitumor properties - Rubbiani, Riccardo; Kitanovic, Igor; Alborzinia, Hamed; Can, Suzan; Kitanovic, Ana; Onambele, Liliane A.; Stefanopoulou, Maria; Geldmacher, Yvonne; Sheldrick, William S.; Wolber, Gerhard; Prokop, Aram; Wölfl, Stefan; et al. (Journal of medicinal chemistry, 2010)
Gold(I) complexes such as auranofin have been used for decades to treat symptoms of rheumatoid arthritis and have also demonstrated a considerable potential as new anticancer drugs. The enzyme thioredoxin reductase (TrxR) is considered as the most relevant molecular target for these species. The here investigated gold(I) complexes with benzimidazole derived N-heterocyclic carbene (NHC) ligands 1a−4a represent a promising class of gold coordination compounds with a good stability against the thiol glutathione. TrxR was selectively inhibited by 1a−4a in comparison to the closely related enzyme glutathione reductase, and all complexes triggered significant antiproliferative effects in cultured tumor cells. More detailed studies on a selected complex (2a) revealed a distinct pharmacodynamic profile including the high increase of reactive oxygen species formation, apoptosis induction, strong effects on cellular metabolism (related to cell surface properties, respiration, and glycolysis), inhibition of mitochondrial respiration and activity against resistant cell lines.
Gesehen am 22.06.2023